Inflammatory potential of diet and risk of pancreatic cancer in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. Issue 12 (2nd February 2018) - Zheng, Jiali; Merchant, Anwar T.; Wirth, Michael D.; Zhang, Jiajia; Antwi, Samuel O.; Shoaibi, Azza; Shivappa, Nitin; Stolzenberg‐Solomon, Rachael Z.; Hebert, James R.; Steck, Susan E.
Abstract : Inflammation plays a central role in pancreatic cancer etiology and can be modulated by diet. We aimed to examine the association between the inflammatory potential of diet, assessed with the Dietary Inflammatory Index (DII®), and pancreatic cancer risk in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial prospective cohort. Our study included 101, 449 participants aged 52–78 years at baseline who completed both baseline questionnaire and a diet history questionnaire. Energy‐adjusted DII (E‐DII) scores were computed based on food and supplement intake. Cox proportional hazards models and time dependent Cox models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) with participants in the lowest E‐DII quintile (most anti‐inflammatory scores) as referent. After a median 8.5 years of follow‐up, 328 pancreatic cancer cases were identified. E‐DII scores were not associated with pancreatic cancer risk in the multivariable model (HRQ5vsQ1 = 0.94; 95% CI = 0.66–1.35; p ‐trend = 0.43). Time significantly modified the association ( p ‐interaction = 0.01). During follow up <4 years, there was suggestive evidence of an inverse association between E‐DII and pancreatic cancer (HRQ5vsQ1 = 0.60; 95% CI = 0.35–1.02; p ‐trend = 0.20) while there was a significant positive trend in the follow up ≥4 years (HRQ5vsQ1 = 1.31; 95% CI = 0.83–2.08; p ‐trend = 0.03). Similar results were observed for E‐DII from food only. Our study does not support an association between inflammatory potential of diet and pancreatic cancer risk; however, heterogeneous results were obtained with different follow‐up times. These divergent associations may result from the influences of undetected disease in the short‐term. Abstract : What's new? Inflammatory conditions including chronic pancreatitis and obesity are risk factors for pancreatic cancer, and diet can modulate inflammation. While the inflammatory potential of diet has previously been associated with pancreatic cancer in two case–control studies, possible recall and selection biases cannot be excluded. Here, the authors examined the association between the inflammatory potential of diet as assessed with the Dietary Inflammatory Index and pancreatic cancer risk in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial prospective cohort. No association was found between inflammatory potential of diet and pancreatic cancer risk; however, heterogeneous results were obtained with different follow‐up times.